Motivasi Belajar dalam Memediasi Pengaruh Lingkungan Teman Sebaya, Kondisi Ekonomi Orangtua terhadap Prestasi Belajar (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the direct influence of the peer environment and the economic conditions of parents through learning motivation on students' accounting learning achievement. The population in the study was students of class 10 Accounting in Batang Regency, which amounted to 143 students. Data was taken by questionnaire. Data were analyzed by descriptive statistical analysis and multiple linear regression analysis. path analysis, and hypothesis testing, namely t test and Sobel test. The results showed: (1) peer environment has a positive and significant effect on learning achievement; (2) parents' economic conditions have no effect on learning achievement, (3) learning motivation has a positive and significant effect on learning achievement, (4) peer environment has a positive and significant effect on learning motivation, (5) parents' economic conditions have no effect on learning motivation , (6) peer environment has a positive and significant effect on achievement through learning motivation, and (7) parents' economic conditions have no effect on learning achievement through learning motivation.